Pelaksanaan Fungsi-Fungsi Manajemen Di Lembaga Pendidikan Dalam Meningkatkan Mutu Pendidikan - Anis Zohriah; Ishlah Farah Diba (Journal on Education, 2023)
Effective and efficient management is essential for educational institutions to achieve their educational goals. This article uses a literature review method to discuss the implementation of management functions in educational institutions. The planning function includes strategic, operational, and curriculum development planning. The organizing function involves grouping tasks, workforce, and arranging classroom and laboratory spaces. The implementation function includes teaching, assessment, and student development. Meanwhile, the supervision function includes monitoring and controlling activities to ensure that the set goals are achieved effectively and efficiently. Through the implementation of these management functions, educational institutions can produce high-quality human resources and graduates who are ready to face future challenges. Therefore, decision-makers in educational institutions must pay attention to the implementation of management functions so that educational goals can be maximized.